دور المحاسب الإداري في تفعيل حوكمة المؤسسات بالجزائر - جلاخ, حسين; حمادي, نبيل (University of Eloued جامعة الوادي, 2019)
هدفت هذه الدراسة إلى توضيح الدور الذي يؤديه المحاسب الإداري في دعم تنفيذ أليات الحوكمة بالبيئة الجزائرية، من خلال توزيع وتحليل استبيان بعينة من المؤسسات الاقتصادية والممارسين لمهنة التدقيق والمحاسبة. توصلت هذه الدراسة إلى أن ممارسات المحاسبة الإدارية في عينة الدراسة تفتقد إلى الاستقلالية، فالمحاسب الإداري يمارس نشاطه من خلال مصلحة المحاسبة التحليلية التابعة لقسم المالية والمحاسبة، ويؤدي دور مهم في تنفيذ آلية مجلس الإدارة وآلية الإفصاح والشفافية . وقد أوصت هذه الدراسة بضرورة إنشاء قسم خاص بالمحاسبة الإدارية تابع مباشرة إلى مجلس الإدارة، وإشراك المحاسب الإداري أكثر في عملية الإفصاح والشفافية لتحسين جودة التقارير المالية Abstract: This study aimed at clarifying the role played by the management accountant in Governance mechanisms implementation of in Algeria using the analysis of questionnaire in a sample of Algerian institutions and accounting and auditing practitioners. This study concluded that the management accounting practices in the study sample lack the concept of independence. Therefore, the management accountant performs his functions through the analytical accounting service of the finance and accounting department. He plays an important role in implementing the mechanism of the board of directors, disclosure and transparency. This study recommended the need to establish a specific department for management accounting that is related to the Board of Directors in order to involve the management accountant in the process of disclosure and transparency for the sake of improving the of financial reports’ quality
The Role of Management Accountant in activating corporate Governance in Algeria
مقال - مجلة رؤى اقتصادية
Keywords: محاسب إداري، مجلس الإدارة، إفصاح، شفافية. الترميز الاقتصادي ) JEL :) G3, M110, M410; Management Accountant; Board of Directors; Disclosure; Transparency. Jel Classification Codes : G3, M110, M410.